The introduction of the Stanford-Binet intelligence scales in Paraguay - José E. García (Interacciones)
Although the first strategies to evaluate the human intellectual skills find millennial precedents in the ancient China, the attempts of measurement in the modern period began with the English psychologist Francis Galton in the decade of 1880, applying physiological measurements to estimate the human talent. At the beginning of the XXth century, the French psychologists Alfred Binet and Théodore Simon constructed the first metric scales to calculate children’s intelligence. These were later modified in the United States by Lewis Terman, who published the most known and influential review. In Latin America and other regions of the world the local adaptations took place at the same time. In Paraguay, the Stanford-Binet test was introduced in the decade of 1920 by the school teacher Ramón Indalecio Cardozo. He did not limit himself to an uncritical reproduction, but realized some modifications to adapt the scale to the local culture and improve its reliability. This article studies the introduction of the Stanford-Binet test to the general context of the Paraguayan education and Cardozo's adaptations. To achieve this, we proceed to a review of primary and secondary sources, putting ideas and concepts in its correct historical context. It also contributes to extend previous papers focused on the author’s works and Paraguayan psychology during the pre-university period.